Penandaan dan Pemaknaan Teritorial di Kantin Sastra bagi Mahasiswa Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia - Erikha, Fajar (Paradigma: Jurnal Kajian Budaya, 2017)
This study explores the phenomenon of marking (signifying) and meaning of territorial at Kantin Sastra (Kansas) by undergraduate students of Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia. Territory as a social space is formed through a process of semiosis preceded sensory knowing in identifying signs, repeatedly making representations in cognition that become the signifying order of the cultural semiotic on some students. Research using micro semiotic perspective and trichotomy of signs by Charles Sander Peirce. Through micro semiotic perspective, a number of particular findings will be analyzed to get a synthesis (inductive), whereas the approach of Peirce perspective explains the signs through the trichotomies: representamen represented through qualisigns, sinsigns, and legisigns; representation, represented by icons, indexes, and symbols; interpretant represented by rhemes, dicisigns, and arguments. As a result, there is a territorial signifying and meaning of Kansas by the undergraduate student of Fakultas Ilmu Pengetahuan Budaya Universitas Indonesia.